Numerical investigation of scale effect of nominal wake of four-screw ship. (1st July 2019) - Sun, Shuai; Chang, Xin; Guo, Chunyu; Zhang, Hongyu; Wang, Chao
Abstract: An experimental investigation is conducted to obtain the nominal wake of a four-screw ship in a towing tank using a particle image velocimetry (PIV) measurement system. A computational study on the viscous flow fields of the ship at different scales is carried out using the Reynolds-averaged Navier–Stokes (RANS) method, without considering the free surface effect. The scale effect for the axial nominal wake field of the inside and outside propeller discs is analyzed in detail. The results show that the CFD results and PIV data are in good agreement. Different circumferential distribution patterns of the axial nominal wake field exist between the inside and outside propeller discs, especially in the zone behind the brackets. The mean wake fraction of the inside propeller is generally larger than that of the outside propeller when different radii are considered. For both the inside and outside propellers, the mean axial wake fraction is relatively large in the inner radius area (0.3 ≦ r/R ≦ 0.6), whereas it is relatively small and almost coincident in the outer radius area (0.7 ≦ r/R) at different scales. ω x (Axial wake fraction) decreases nonlinearly with the increase in Reynolds number for both the inside and outside propeller discs, whereas Δ ω x (wake fraction difference) increases linearly with the increase in the Reynolds number. With the increase of the model scale, the harmonics components decreases gradually.